If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7b=3(b+4)
We move all terms to the left:
7b-(3(b+4))=0
We calculate terms in parentheses: -(3(b+4)), so:We get rid of parentheses
3(b+4)
We multiply parentheses
3b+12
Back to the equation:
-(3b+12)
7b-3b-12=0
We add all the numbers together, and all the variables
4b-12=0
We move all terms containing b to the left, all other terms to the right
4b=12
b=12/4
b=3
| 5x-15=7x+11 | | x+-2.5=14-2 | | (x+4)*6=48 | | x/4+x/2=3 | | 25+3b-11=74 | | 2(x^2+12x-864)=0 | | X/4=x/2+3 | | 2x^27=15x | | 3-x/4=x/2 | | 5-(4x-6)=2x | | 2x=365/4) | | x^2+9x+15=(x^2+15) | | 2x-54x^-2=0 | | A-3=5b | | 2x(1-27x^-1)=0 | | 7x+12x=90 | | X-3=1/2x | | 0.5x3+173611.212743x2+0.000052455x-0.00000000714=0 | | 4/5x-1=0 | | x-0,15x=125 | | 4x-x2=0 | | 3x^2-9x-6=3x-6 | | 3x-2=7x= | | (x/2+9x+15)=(x+5)^2 | | 5x+x+1=13 | | 2x-x/2-3=0 | | n-3/4=-11/8 | | n-3/3=-11/8 | | 6x^=36x | | 10x+5=13x+6x | | n-3/4=11/8 | | 5x-18=3x+24 |